P408 Anti-Drug Antibodies Detected in the Presence of Adequate Infliximab Drug Levels In IBD Patients in Clinical Remission have Limited Clinical Significance. (27th May 2021) - Doherty, J; Varley, R; Healy, M; Dunne, C; Mac Carthy, F; McKiernan, S; Hartery, K; Kevans, D
Abstract: Background: Immunogenicity, with the development of antibodies-to-infliximab (ATI) increases drug clearance and can lead to loss of infliximab (IFX) response in inflammatory bowel disease(IBD). Reporting of ATI is variable between commercial assays with some assays having high sensitivity for low-titre antibodies. Uniform thresholds for clinically relevant antibody titres are lacking. It is unclear how ATI affect treatment outcome when adequate trough IFX concentrations are present and ATI are detected. Methods: We aimed to assess the impact of ATI detected in the presence of adequate IFX levels on the outcome of IFX therapy in IBD patients in clinical remission. A proactive therapeutic drug monitoring(TDM) strategy was utilized in our unit with IFX and ATI levels, assessed at trough, in all IBD patients receiving IFX. Baseline demographics were collected. Patients were grouped based on disease activity. An adequate trough IFX level was a concentration > 3 µg/mL, with low levels defined as < 3 µg/mL. ATI positivity was defined as a concentration > 10 AU/mL. Receiver operating characteristic analysis was performed to evaluate the classifying performance of ATI concentration for low IFX levels. Survival analysis was performed to determine IFX persistence in patients with adequate IFX levels and positive ATI. Follow up TDM assessments, where available, were documented to determine changes in ATI concentration over time in patients with adequate IFX levels. Results: 108 patients were included. Median age 36years. 46% were female. 36% had ulcerative colitis, 60% Crohn's disease. 35% were receiving concomitant immunomodulators. 56% of patients were in remission at the time of TDM assessment. 44%, 30% and 26% of patients had IFX levels < 3 µg/mL, 3 – 7 µg/mL and > 7 µg/mL. Median [range] ATI concentration was 11 AU/mL [0 – 800]. ATI positivity occurred in 25%, 19% and 8% of IFX groups with levels < 3 µg/mL, 3 – 7 µg/mL and > 7 µg/mL. There was a weak inverse correlation between trough ATI and IFX concentration (p=0.01)(Figure 1). ATI concentration performed poorly as a classifier of low IFX levels (AUC 0.568)(p=0.39). 83%(15/18) of IBD patients in remission with adequate IFX levels and positive ATI remained on IFX for the duration of follow up with a mean cumulative time on IFX of 111.2 weeks (95% CI 105.1 – 117.3)(Figure 2). In this group, there was no significant change in ATI titre comparing index with follow up TDM assessments (p=0.14)(Figure 3). Conclusion: ATI positivity in the presence of adequate IFX levels is common with proactive TDM. For patients in clinical remission ATI positivity in the presence of adequate IFX levels has limited clinical significance. Care should be taken to avoid unnecessary therapy alterations in this patient subgroup.